Genotype and sex effects on carcass and meat quality of suckling kids protected by the PGI "Cabrito de Barroso" - Santos, Virgínia (2007)
Carcass composition and meat quality traits were evaluated in 55 suckling kids (27 males and 28 females) from Serrana (S), Bravia (B) and Serrana x Bravia (SxB) crossbred genotypes. Kids were slaughtered at 8-11 kg of live weight according to "Cabrito de Barroso-PGF" specifications and carcasses' left sides were totally dissected. Dressing percentage (based on ELW) did not vary between genotypes and sexes. Genotype B carcasses have better conformation, expressed in higher compactness index and muscle/bone ratio. Sex had no effect on the composition of dissected carcass but females deposited more internal fat than males. S genotype had significantly less muscle content and higher dissectible fat compared to B and SxB genotypes, suggesting differences in maturity stages. The carcass' bone content (20.4-21.4%) did not differ significantly between genotypes. The longissimus thoracis et lumborum (LTL) and gluteobiceps (GB) muscles were used for meat quality determinations. Genotype had a significant effect on meat traits and fatty acid composition of the analysed muscles: B genotype and LTL muscle showed lower final pH, SxB genotype had darker and more red muscles, GB muscle had a higher shear force value and lower collagen solubility. Few sex effects were observed on meat quality traits as well as on fatty acid composition. Average percentage of desirable fatty acids in kids was superior to 60% with male S genotype displaying a lower value. Genotypes B and BxS, males and GB muscle had more favorable PUFA:SFA ratios